Occupational motivation of music teachers as significant factor of social wellbeing - Giedrė Gabnytė; Diana Strakšienė (Social Welfare: Interdisciplinary Approach)
The article deals with the peculiarities of manifestations of music school teachers’ occupational motivation as a significant factor of social wellbeing. It presents the results of questionnaire survey of teachers: professional satisfaction estimates are given, peculiarities of collaboration of participants in the process of education are revealed, and evaluations of health, work conditions, and material interest of teachers are provided.